Laïcité et christianisme chez Émile Poulat - Morozzo della Rocca, Roberto (Chrétiens et Sociétés. Documents et Mémoires, 2020)
Émile Poulat, sociologist, historian, unclassifiable intellectual, who can never be pigeonholed a priori, has marked during his long life (Lyon 1920 - Paris 2014) the never-exhausted French and European debate on the relationship between secularism and religion, between modernity and Christianity. This book discusses the basic subjects of his scientific production, as well as his working method based on a cold objectivity opposed to subjective passions, without which his work would probably have been less fruitful. In the construction of his main theses, which have made him a disturbing intellectual, Poulat has always challenged commonplaces, starting with the dualistic schemes of explaining politics and religion in terms of right/left, conservatism/progressism, archaism/modernity, faith/atheism. The result is a work that is outside the usual patterns, that poses more questions than it provides certainties, and yet is fascinating for those who seek a greater interpretive depth above the fray. In this book, we move along a double track, between the researcher Poulat and the man Poulat, by illuminating the link between the two, to show the coherence of his work and his life.